Learning to Lead as Learning to Learn: The Experiences of Malay Women at Malaysian Public Universities - Norseha Unin; John Dirkx (Adult Education Research Conference, 2011)
This study examined how Malay women learn to lead within their social context. Two semi-structured interviews were conducted with four deans and two directors from Malaysian public universities. The findings demonstrate the paradoxical contexts that these women faced in learning to lead, and how they learned to navigate the multiple tensions and contradictions they faced in assuming leadership roles. For them, learning to lead is about learning to learn from and through tensions and contradictions. We discuss the implications that the findings hold for conceptions of informal learning, especially as reflected in the social context of women within nonwestern societies.
Keywords: Informal Learning; Social Context